Reanimation of the paralyzed lids by cross-face nerve graft and platysma transfer. Issue 3 (March 2018) - Biglioli, Federico; Zago, Matteo; Allevi, Fabiana; Ciprandi, Daniela; Dell'Aversana Orabona, Giovanni; Pucciarelli, Valentina; Rabbiosi, Dimitri; Pacifici, Ilaria; Tarabbia, Filippo; Sforza, Chiarella
Abstract: Alterations of facial muscles may critically humper patients' quality of life. One of the worst conditions is the reduction or abolition of eye blinking. To prevent these adverse effects, surgical rehabilitation of eyelid function is the current treatment choice. In the present paper, we present a modification of the technique devised by Nassif to recover lids from long-standing paralysis. In our modification, the upper lid is rehabilitated by a platisma graft innervated by the contralateral facial nerve branches using a cross-face sural nerve graft. The lower lid is pulled upward by a fascia lata string suspension. Fourteen patients with unilateral facial paralysis were operated on consecutively. For each patient, two sets of frontal photographs with open and closed eyes were available, before and after the surgical rehabilitation. On average, eyelid lumen with closed eyes decreased by 2.6 mm (SD 2.4) after surgical rehabilitation (37% of the initial value). With open eyes, the decrement was 1.5 mm (SD 1.6, 15%). The modifications were highly significant (p < 0.01), with very large effect sizes. Reanimation of the paralyzed eye by mean of cross-face nerve graft followed by platisma neurotization can restore natural eyelid closure and blink reflex.